GOLD INVESTMENT IN A SYARIAH PORTGAGE DURING THE COVID-19 PANDEMIC TIME - Syamsud Dhuha; Hardian Tri Cahyadi; Muhammad Atourrahman (Cross-Border Journal of Business Management, 2021)
During the Covid-19 pandemic gold pawning became the mainstay of the community. This trend is evident from the recorded transaction data at pawnshops and Islamic banks offering gold pawn services. Gold investment that is not eroded by inflation, price trends that continue to increase, flexible sale and purchase transactions, make gold an alternative investment option. The purpose of this study is to determine and describe gold investment in Islamic pawnshops during the Covid-19 pandemic as protection against assets. The method used in this research is descriptive, with library research. The results of this study indicate that gold investment in sharia pawnshops from sharia gold pawning, which was originally only an alternative financing and additional capital in the short term, has started to be used as a means of investing, by taking advantage of the increase in the value of gold prices and the convenience and relief of Islamic gold pawning. Investing in gold by buying, storing and then selling it using a pawning service, namely by buying, saving and then pawning is a strategy for investing in gold as well as a solution to maintaining gold investment.